La dimension territoriale du développement durable - Shana Sabbado Flores; Rosa Maria Vieira Medeiros (Confins)
Working the theme sustainability is a challenge required in all sectors of society, due to the intensification of environmental and social problematic and their consequences. This paper analyzes the theoretical and methodological resources offered by the territorial approach to working with sustainability and proposes perspectives for the integration of these concepts, based on researches developed in France, Italy and Brazil. In general, it can be observed that sustainability can’t be separated from its context, is directly related to the identity and the history, therefore, is linked with the territory and its territorialities. Also, it is at the local level, or in the territory, that many impacts are presented and where actions can be performed, even if the issues are global. Thus, the territorial approach integrates the dimensions, contextualizes the issues and promotes the actions, which justifies the adherence of the territorial approach, or the importance of the territorial dimension of sustainability.